The Harlequin Years: Music in Paris 1917-1929 - Nichols, Roger (Berkeley, CA London University of California Press Thames and Hudson, 2002)
Few decades in the life of any European city have been as rich in musical personalities and achievements as the 1920s in Paris. It was, as Stravinsky said, the hub of the musical world, popular for travelers because it was cheap. Composers working in or near the city included Ravel, Fauré, Satie, Stravinsky, and Prokofiev as well as the up-and-coming members of Les Six, most notably Poulenc, Milhaud, and Auric. Among their collaborators were the painters Picasso, Braque, Dufy, and Juan Gris, while Jean Cocteau kept a watchful eye on new trends. Horowitz, Robert Casadesus, and Vlado Perlemuter all made their Paris debuts in this decade, as did the young violin prodigies Ginette Neveu and Yehudi Menuhin. Women musicians were coming into their own: the composers Germaine Tailleferre and Lili Boulanger, salon hostesses like the Princesse de Polignac and Mae Clemenceau. The Harlequin Years charts a nimble course through this remarkable era, noting currents as well as personalities, telling stories as well as pondering the occasional philosophical problem.Through the whole book runs the double thread spun by Jean Cocteau in his little volume Le coq et l'harlequin: the warp of the traditional French cock being pulled by the weft of the foreign, multicolored harlequinade. Roger Nichols's spirited narrative shows that this was also an uncertain time, as the war had cast doubt on old assumptions. Did wisdom necessarily come with age? Were hierarchies necessary? Irreverence was in, the circus was aesthetically at least as valuable as the finest symphony orchestra. Against all this some composers, like Fauré and Roussel, continued with traditional forms, though each brought to them his own highly personal language and syntax.
Keywords: 20th Century (1901-2000); Music history; Cultural history; Paris (France)